(untitled) (The Review of Diabetic Studies, 2025)
Background: Dental imaging is indispensable in oral healthcare; however, exposure to ionizing radiation poses cumulative biological risks to patients and healthcare workers. Adherence to radiation protection principles is therefore critical. Interprofessional collaboration between dental and nursing professionals necessitates a shared and adequate level of radiation safety awareness. Aim: This study aimed to assess knowledge, attitudes, and practices related to radiation safety in dental imaging among dental and nursing professionals in Saudi Arabia. Methods: A descriptive cross-sectional study was conducted among 350 dental and nursing professionals working in governmental and private dental facilities in Saudi Arabia. Data were collected using a validated self-administered questionnaire. Descriptive statistics, independent t-tests, chi-square tests, and Pearson correlation were used for analysis. Results: The overall mean knowledge score was 71.3 ± 11.9. Dental professionals demonstrated significantly higher knowledge scores than nursing professionals (75.8 ± 10.6 vs. 65.9 ± 12.1, p < 0.001). Adequate radiation safety practice was reported by 68.6% of participants. Years of experience showed a moderate positive correlation with knowledge scores (r = 0.41, p < 0.001). Conclusion: Radiation safety awareness among dental and nursing professionals in Saudi Arabia was moderate, with significant interprofessional differences. Continuous education and structured training programs are strongly recommended to enhance radiation protection practices in dental settings.